A Revised Interpersonal Circumplex Inventory of Children's Social Goals. (February 2013) - Trucco, Elisa M.; Wright, Aidan G. C.; Colder, Craig R.
Motivational factors such as social goals are important features of developing social adjustment, and thus researchers studying social adjustment need psychometrically sound measures of social goals. A valid measure of social goals for English-speaking youth is lacking. Such a measure would increase understanding of children's social adjustment and allow for testing developmental models of social goals and interpersonal functioning. The authors' aim was to revise the Interpersonal Goals Inventory for Children (IGI-C) for an English-speaking sample and examine its validity. The revised IGI-C (IGI-CR) fit a circumplex model and performed as expected with most external criterion variables examined. In addition, some differences were observed across males and females, offering insights into gender differences in social goals. Results support the IGI-CR as a sound measure.